(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we demonstrate how series representation for the three basic univalent G-functions, namely G1;00;2; G1;11;2 and G1;11;1, can be obtained from their Mellin-Barnes path integral representations.In two special cases, images of third basic univalent G-function, G1;1,1;1 are derived by the Biernacki and Libera operators.